2006
DOI: 10.1055/s-2006-947246
|View full text |Cite
|
Sign up to set email alerts
|

Aachener Sprachanalyse (ASPA): Evaluation bei Patienten mit chronischer Aphasie

Abstract: ZusammenfassungHintergrund: Ziel der vorliegenden Studie war, die Aachener Sprachanalyse (ASPA) als ein neues und viele Parameter umfassendes Spontansprachanalysesystem anhand der Testgütekrite-rien Objektivität, Reliabilität und Validität zu evaluieren. Methode: Die Spontansprache von 16 chronischen Aphasikern wurden zu drei Zeitpunkten (zweimal vor und einmal nach zweiwöchi-ger Intensivtherapie) mit ASPA evaluiert. Zudem wurden Transkripte von gesunden Kontrollen mit ASPA ausgewertet. Die Inter-und Intrarate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, no significant differences were present between groups. These findings replicate previous studies that report substantial improvement in language functions and measures of connected speech after CIAT in patients with different aphasia syndromes and levels of aphasia severity (Barthel et al, 2006;Maher et al, 2006;Meinzer et al, 2005;Pulvermueller et al, 2001). These results also agree with previous evidence of effective treatment provided by trained laypersons (David et al, 1982;Lesser et al, 1986;Marshall et al, 1989;Meikle et al, 1979;Shewan & Kertesz, 1984;Wertz et al, 1986;Worrall & Yiu, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, no significant differences were present between groups. These findings replicate previous studies that report substantial improvement in language functions and measures of connected speech after CIAT in patients with different aphasia syndromes and levels of aphasia severity (Barthel et al, 2006;Maher et al, 2006;Meinzer et al, 2005;Pulvermueller et al, 2001). These results also agree with previous evidence of effective treatment provided by trained laypersons (David et al, 1982;Lesser et al, 1986;Marshall et al, 1989;Meikle et al, 1979;Shewan & Kertesz, 1984;Wertz et al, 1986;Worrall & Yiu, 2000).…”
Section: Discussionsupporting
confidence: 90%
“….91 for all subtests in chronic aphasia patients; Huber et al, 1983). Moreover, Barthel et al (2006) demonstrated stability of language impairment across two repeated baseline assessments in chronic patients with aphasia. Significant improvement was substantiated after a subsequent 2-week intensive treatment interval.…”
Section: Discussionmentioning
confidence: 88%
“…In another study, Barthel et al 25 assessed the impact of intensive speech and language therapy (CI-based and MOAT) on connected speech measures. Speech samples were obtained from 12 patients (spontaneous speech scales of the AAT; standard picture descriptions) across two baseline trials prior to treatment and immediately after treatment.…”
Section: Clinical Evaluation In Chronic Aphasia (See Table 1 For a Sumentioning
confidence: 99%
“…We did not assess baseline stability of language functions across repeated sessions: However, patients were in the late chronic stage of aphasia (average onset: 51.6 months; range: 12-156 months) and one would not expect substantial improvement of language function without training (Robey, 1998). Moreover, only recently we assessed the stability of connected speech measures in 16 patients with chronic aphasia across a 2-day baseline interval (Barthel, Djundja, Meinzer, Rockstroh, & Eulitz, 2006), which yielded comparable results, while substantial improvement after 2 additional weeks of intensive training was observed. Therefore, we are confident that the improvement found in our sample can be attributed to the training provided.…”
Section: Effective Elements In Aphasia Therapy 417mentioning
confidence: 99%